2008
DOI: 10.2147/cia.s1681
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of neuropathic pain in older persons

Abstract: . However, no particular consideration is given as to how the recommendations are applicable to the elderly population. This paper will review the guidelines in relation to this population and evaluate the existing evidence relating to the use of these drugs in older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Regarding pharmacology, of the studies identified, there were a variety of pharmacologic agents used in treating pain in older adults including analgesics, psychiatric medications, and a number of adjuvant medications. However, selection of drug therapy requires an understanding of age-related pharmacodynamics and pharmacokinetic changes and needs to take into account any coexisting diseases and use of over-the-counter medications ( Haslam & Nurmikko, 2008 ; Pokela et al., 2010 ). Age-related alterations in drug distribution, excretion, and metabolism may lead to a longer duration of action and decreased or increased plasma concentration for many pain medications.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pharmacology, of the studies identified, there were a variety of pharmacologic agents used in treating pain in older adults including analgesics, psychiatric medications, and a number of adjuvant medications. However, selection of drug therapy requires an understanding of age-related pharmacodynamics and pharmacokinetic changes and needs to take into account any coexisting diseases and use of over-the-counter medications ( Haslam & Nurmikko, 2008 ; Pokela et al., 2010 ). Age-related alterations in drug distribution, excretion, and metabolism may lead to a longer duration of action and decreased or increased plasma concentration for many pain medications.…”
Section: Discussionmentioning
confidence: 99%
“…Data on antineuropathic analgesic agents in the older population for GpIR raise concern regarding the same issue of relative age and pharmacodynamics. 23 Bowel absorption is altered in the elderly, multiple medications are coprescribed, and underlying physiological systems are increasingly fragile. Where comparative data exists for immediate release preparations, GpIR is generally considered safer than TCA; however, where administered as GpEn, no specific data exists.…”
Section: Safety and Tolerability Issuesmentioning
confidence: 99%
“…Where comparative data exists for immediate release preparations, GpIR is generally considered safer than TCA; however, where administered as GpEn, no specific data exists. 23 …”
Section: Safety and Tolerability Issuesmentioning
confidence: 99%
“…Although generally regarded as being well tolerated, both drugs can nevertheless induce side effects that might considerably interfere with quality of life and patient safety 2,8,9. As psychoactive compounds, their use might be associated with cognitive impairment, drowsiness, and dizziness, particularly in the elderly population 9.…”
Section: Introductionmentioning
confidence: 99%
“…Although generally regarded as being well tolerated, both drugs can nevertheless induce side effects that might considerably interfere with quality of life and patient safety 2,8,9. As psychoactive compounds, their use might be associated with cognitive impairment, drowsiness, and dizziness, particularly in the elderly population 9. Consequently, they might increase the risk of falls or further aggravate the detrimental neurological effects (drowsiness, sedation, somnolence) of other centrally acting medications such as opioids, antidepressants, or sedatives 10,11.…”
Section: Introductionmentioning
confidence: 99%